Some results of studying the effectiveness of vaccination against hepatitis B - L. V. Rubis (Журнал инфектологии, 2020)
With the increase in period of time from the beginning of vaccination against hepatitis B the relevance of the question about the duration of post-vaccination immunity increases.The study has aimed to evaluate post-vaccination humoral  immunity to hepatitis b virus 3–9 and 10–17 years after vaccination.Materials and methods. The level of antibodies to HBsAg was studied in 25 children aged 3–4 years and 104 adolescents aged 16–17 years who were vaccinated in the first year of life, as well as 79 adults who were vaccinated at different times over 17 years. Vaccination was carried out according to the scheme: 0-1-6 months with different recombinant vaccines. The test systems “Vectonvsad-antibodies” produced by JSC “Vector-best” were used for the study.Results. Antibody titers below 10 IU / l were found in 49,0±4,9% of adolescents and 50,0±8,6% of adults vaccinated over 10–17 years, 56,4±8,0% of adults vaccinated over 3–9 years, and 60,0±9,8% of children vaccinated over 3–4 years prior to the study. Antibodies in titers above 10 mIU/ml were detected only in isolated cases. No cases of hepatitis b virus infection or transmission were registeredamong the surveyed individuals.The low level of anti-HBs was not associated with specific names of vaccines and their storage conditions, with longer intervals between vaccinations. There was a slight decrease in the immune response in people over 40 years of age. The significant proportion of people who do not have a protective level of anti-HBs among those who have been vaccinated three times, identified in our and a number of other published studies, requires further study. In General, among the population of the Republic, the incidence of all forms of infection in the last decade against the background of mass  vaccination has had a pronounced downward trend.